What makes it a heap? - Williamson, T (Kluwer Academic Publishers, 1996)
On the epistemic view of vagueness, a vague expression has sharp boundaries whose location speakers of the language cannot recognise. The paper argues that one of the deepest sources of resistance to the epistemic view is the idea that all truths are cognitively accessible from truths in a language for natural science, conceived as precise, in a sense explained. The implications of the epistemic view for issues about the relations between vague predicates and scientific predicates are investigated.